Guru sebagai Fasilitator dalam Pembelajaran Daring ditinjau dari Perspektif Kristen - Kristina Simamora; Wiyun Philipus Tangkin (Sekolah Tinggi Teologi Bethel Ambon, 2021)
The role of the teacher as a facilitator aims to provide freedom of learning for students. This role adheres to humanistic learning theory, namely students as centers, teachers as escorts, and facilitators in learning. In the implementation of online learning, teachers only give and collect assignments from students, and education is done without the teacher's help. This shows that the teacher is not adequately performing his role as a facilitator. This paper was written using a research method of literature review with the formulation of the problem of how teachers' role as facilitators in online learning to write to find out how teachers should perform their role as facilitators for elementary school students in online learning. From a Christian perspective, learning is done christ-centered and student-oriented. As a person who has been redeemed, the teacher has a responsibility to introduce students to God; one way is to carry out his role as a facilitator well. The role of teachers as facilitators that can be applied in online learning includes accompanying, directing, listening, making time for students. It is recommended that authors, teachers, and researchers who will continue this research should carry out the role of teachers as facilitators responsibly through the use of available platforms such as teams, zoom, and video calls. AbstrakPeran guru sebagai fasilitator bertujuan memberikan kebebasan belajar bagi siswa. Peran ini, menganut teori belajar humanistik, yaitu siswa sebagai pusat, guru sebagai pendamping dan fasilitator dalam pembelajaran. Dalam pelaksanaan pembelajaran daring terdapat guru hanya memberikan dan menagih tugas dari siswa dan pembelajaran dilakukan tanpa dampingan guru. Hal ini menunjukkan bahwa guru tidak menjalankan perannya sebagai fasilitator dengan baik. Makalah ini ditulis menggunakan metode penelitian kajian literatur dengan rumusan masalahnya adalah bagaimana peran guru sebagai fasilitator dalam pembelajaran daring dengan tujuan penulisan untuk mengetahui bagaimana seharusnya guru menjalankan perannya sebagai fasilitator bagi siswa sekolah dasar dalam pembelajaran daring. Berdasarkan perspektif Kristen, pembelajaran dilakukan dengan berpusat kepada Kristus dan berorientasi kepada siswa. Guru sebagai pribadi yang telah ditebus, memiliki tanggung jawab untuk mengenalkan siswa kepada Allah, salah satu caranya adalah dengan melaksanakan perannya sebagai fasilitator dengan baik. Peran guru sebagai fasilitator yang dapat diterapkan dalam pembelajaran daring di antaranya, mendampingi, mengarahkan, mendengarkan, menyediakan waktu untuk siswa. Disarankan kepada penulis, guru dan peneliti yang akan melanjutkan penelitian ini hendaknya melaksanakan peran guru sebagai fasilitator dengan bertanggung jawab melalui melalui penggunaan platform yang tersedia seperti teams, zoom, dan video call.